Serious fungal infections in Portugal - Sabino, Raquel (2018)
There is a lack of knowledge on the epidemiology of fungal infections worldwide because there are no reporting obligations. The aim of this study was to estimate the burden of fungal disease in Portugal as part of a global fungal burden project. Most published epidemiology papers reporting fungal infection rates from Portugal were identified. Where no data existed, specific populations at risk and fungal infection frequencies in those populations were used in order to estimate national incidence or prevalence, depending on the condition. An estimated 1,510,391 persons develop a skin or nail fungal infection each year. The second most common fungal infection in Portugal is recurrent vulvovaginal candidiasis, with an estimated 150,700 women (15-50 years of age) suffering from it every year. In human immunodeficiency virus (HIV)-infected people, oral or oesophageal candidiasis rates were estimated to be 19.5 and 16.8/100,000, respectively. Candidaemia affects 2.19/100,000 patients, in a total of 231 cases nationally. Invasive aspergillosis is less common than in other countries as chronic obstructive pulmonary disease (COPD) is uncommon in Portugal, a total of 240 cases annually. The estimated prevalence of chronic pulmonary aspergillosis after tuberculosis (TB) is 194 cases, whereas its prevalence for all underlying pulmonary conditions was 776 patients. Asthma is common (10% in adults) and we estimate 16,614 and 12,600 people with severe asthma with fungal sensitisation and allergic bronchopulmonary aspergillosis, respectively. Sixty-five patients develop Pneumocystis pneumonia in acquired immune deficiency syndrome (AIDS) and 13 develop cryptococcosis. Overall, we estimate a total number of 1,695,514 fungal infections starting each year in Portugal.